Facial indicator in the determination of maxillary central incisor length in Nepalese population – A clinical study - Suraksha Shrestha; Santosh Kumar Yadav (Asian Journal of Medical Sciences, 2022)
Background: The maxillary anterior teeth are important in achieving pleasing facial and dental esthetics. Among those, the central incisor has a key role in determining the esthetic as they are the most dominant and visible teeth during smile. Determining the proper size of these teeth is important but difficult in the absence of pre extraction records in edentulous condition.